Role of Gender Equity and Disability Inclusion to Help Achieve the Larger Cause of Health for All and Attain SDG 2030 by India - Sonali Kar; Abu Bashar; Sridevi Gnanasekaran; A K Jayasree; Pillaveetil Sathyadas Indu; Kajal Srivastava (Indian Journal of Community Medicine)
Gender equality had been targeted under Millennium Development Goals 2015 as Goal 3, whose primary focus was women’s education. It was further reinforced under the ambit of Sustainable Development Goal 5 as again gender equality and women empowerment, whose timeline is by 2030. The review article essays the journey of this very pertinent theme, from abeyance to gaining prominence, and the associated societal variations. Gender equity now is the finer version, which is accepted and received well too, and this inclusiveness has urged us to add disability inclusion into our context of discussion. These issues are always challenges that crop up in the path of development and evolution. Hence, it is very essential that deliberations are conducted to get an insight into the deviations at the regional as well as rural areas in terms of addressing these issues. With appreciable improvement in health-related targets, these issues are coming to the fore, as barriers to sustainable improvements. Hence, developing strategies for gender equity and disability inclusion are likely to play vital roles in the overall goal of Health For All (HFA).